Barostat or syringe‐assisted sensory biofeedback training for constipation with rectal hyposensitivity: A randomized controlled trial. Issue 3 (24th August 2021) - Rao, Satish S. C.; Yan, Yun; Erdogan, Askin; Coss‐Adame, Enrique; Patcharatrakul, Tanisa; Valestin, Jessica; Nag Ayyala, Deepak
Abstract: Background: Rectal hyposensitivity (RH) is a well‐known pathophysiological dysfunction in chronic constipation. Whether biofeedback training improves RH and restores bowel function is unknown. Aim: To investigate the efficacy of barostat‐assisted sensory training (BAST) with syringe‐assisted sensory training (SAST) in patients with RH in a randomized controlled trial. Methods: Patients with RH and chronic constipation (Rome III) were randomized to receive 6 biweekly sessions of BAST or SAST. Verbal/visual feedback was provided during repeated rectal distensions to improve defecation desire/urge and first sensations with either 10‐cm balloon connected to barostat (BAST) or 4‐cm balloon connected to syringe and manometry probe (SAST). Sensory thresholds, bowel symptoms, and therapist and patient's rating of treatments were compared. The primary outcome (responders) was the improvement in ≥2 sensory thresholds. Results: Sixty‐six patients were enrolled: 32 received BAST, 34 received SAST, and 56 completed study. There were significantly more responders in BAST group than SAST (78% vs. 53%, p  = 0.0320). Rectal sensation normalized in 81% with BAST compared to 56% with SAST ( p  = 0.0270). When compared to baseline, desire and urge to defecate thresholds and bowel satisfaction improved with BAST ( p  = 0.0013; p  = 0.0002; p  = 0.0001) and SAST ( p  = 0.0012; p  = 0.0001; p  < 0.0001) and number of complete spontaneous bowel movements with BAST ( p  = 0.0029) but without inter‐group differences. Therapists rated BAST as superior to SAST ( p  < 0.0001), but patients rated both equally. Conclusions: Sensory biofeedback training was effective and significantly improved rectal sensation and constipation symptoms. Although both techniques were useful, the novel BAST was more efficacious and easier to administer for treating RH. Abstract : Background : Rectal hyposensitivity (RH) is a well‐known pathophysiological dysfunction in chronic constipation whose treatment remains challenging. Aim : Investigate the efficacy of barostat‐assisted sensory training (BAST) with syringe‐assisted sensory training (SAST) in RH in a randomized controlled trial. Methods : Patients with RH and chronic constipation (Rome III) randomly received 6 biweekly, verbal/visual sensory biofeedback training with either 10 cm balloon connected to barostat (BAST), (Figure 1) or 4 cm balloon connected to a syringe and manometry probe (SAST). Sensations and symptoms were assessed. Results : The primary outcome was achieved and rectal sensory thresholds normalized with BAST, and with a higher ( p  = 0.032) responder rate than SAST (Figure 2). Both treatments improved constipation. Patients rated treatments equally but therapists rated BAST as superior than SAST ( p  < 0.0001). Conclusions : Although both sensory training modalities improved rectal sensation and constipation symptoms, the novel BAST was more efficacious and easier to administer for treating RH, and therefore a preferred treatment.